Water management in Turkish municipalities from the perspective of employees - Derya Çamur; Hüseyin İlter; Murat Topbaş (Turkish Society of Public Health Specialists, 2018)
Objective: The aim of this study is to determine the views of water management employees with regards to the work being done on water management facilities in the municipalities of Turkey. Method: In this descriptive study, 461 employees from 481 municipalities were interviewed (participation rate 95.8%). The data was collected under observation. Results: 42.4% of the participants worked in water management related jobs where their tasks were not directly related to water. 78.6% of participants did not receive any training on water management. No water tank cleaning is done in 0.7% of municipalities. 59.0% of water tank cleaning personnel did not receive any training on this subject. 97.6% of the participants disclosed that chlorine is still being used for water disinfection in their municipalities. However, 88.6% think that water should be chlorinated for disinfection. 10.0% of the participants stated that they worked on water structures inside of buildings. In 77.3% of the municipalities, network water is used for watering public parks and gardens.  Conclusions: Municipalities should hire personnel who have been trained on all stages of water management. Recruitment of certified and trained personnel in the most extreme applications, such as network control and water storage, must be compulsory.